Language Teaching a Means of Cultural Diplomacy: A Framework for Arabic Language Teaching as a Means of Palestinian Cultural Diplomacy in 21st-Century Turkey - ABU JAZAR, JEHAD M.I. (İstanbul Kültür Üniversitesi, 2021)
Cultural diplomacy is profoundly about promoting culture by formal and informal means and actors, for the sake of advancing international relations. As such, language –the treasure-house of culture and its vehicle of transference– and language teaching are deemed crucial means of cultural diplomacy that countries use to provide a good image and build better understanding and communication for better cooperation on bilateral and multilateral bases. In this regard, this study, with reference to the role of language teaching as a means of cultural diplomacy and the current flourishing of Arabic language teaching and learning in Turkey, presents a framework for utilizing Arabic language teaching as a means of Palestinian cultural diplomacy that advances the Palestinian cause in Turkey. The research follows a 'constructive structure' –similar to Lego structure– in which recent arguments are based on the outcomes of earlier ones. Accordingly, a study of primary and secondary sources which presents a conceptual and practical background of language teaching as a means of cultural diplomacy was conducted. Besides, Data about the current endeavors of Arabic language teaching in Turkey regarding the Palestinian cause were collected by interviewing a group of Palestinian teachers and Turkish learners. The findings were applied to the Palestinian cultural traits and the Turkish stance towards the Palestinian cause, Arabs and Arabic language to draw a framework for a strategy of Palestinized Arabic language teaching in 21st-century Turkey. The study has revealed that the richness of the Arabic language and the welcoming Turkish environment are guarantors for the success of the Palestinized Arabic language teaching in contributing to the perseverance of the Turkish public and governmental support to the Palestinian cause, and the strengthening of the Palestinian strategic depth.
Dil Öğretimi Bir Kültürel Diplomasi Aracı: 21. Yüzyıl Türkiye'de Filistin Kültürel Diplomasisi Aracı Olarak Arap Dili Öğretimi İçin Bir Çerçeve
▪ Yüksek lisans tezi.
Keywords: Turkish-Palestine Relations